DEMOKRASI DALAM PANDANGAN YUSUF AL- QARADHAWI - M. Alwin Abdillah (Prodi Tata Negara (Siyasah) IAIN Langsa, 2019)
The theme of democracy is one of the themes that is still interesting to discuss. Various works that deal with democracy have been produced - both by Islamic thinkers and Westerners. Since the arrival of the West to the Islamic world, and along with the progress of the West today, then something that comes from the West has always been an indicator of progress. For this claim so that many countries feel it is important to